HUBUNGAN PERAN TENAGA KESEHATAN, MINAT IBU, DAN KUALITAS PELAYANAN KESEHATAN TERHADAP PEMBERIAN IMUNISASI BOOSTER CAMPAK RUBELLA DI PUSKESMAS PAGAR GUNUNG - olive Franstika Sari; Sendy Pratiwi Rahmadhani; Eka Afrika (Universitas Pahlawan, 2022)
Infectious diseases that can be prevented by immunization (PD3I) are diseases that are expected to be controlled and eradicated by giving vaccines through immunization programs. Follow-up immunizations for BADUTA children (under two years) are needed to maintain a high level of immunity so that they can provide optimal protection. The purpose of this study was to determine the relationship between the role of health workers, mother's interest, and the quality of health services simultaneously on the provision of measles rubella booster immunization to toddlers aged 18–24 months at Pagar Gunung Health Center. This study uses an analytical survey method with a Cross Sectional approach. This research was conducted at Pagar Gunung Health Center, Lahat Regency. With a total sample of 77 respondents, the sampling technique used was accidental sampling. The variables studied were the variable of the role of health workers, the interest of the mother and the quality of service with the provision of measles booster immunization. The results of the Chi-Square test on the role of health workers obtained value 0.001 < = 0.05, the mother's interest variable obtained value 0.000 < = 0.05, and the variable quality of health services obtained value 0.045 < = 0.05, it means that there is a relationship between the role of health workers, maternal interests and the quality of health services on the provision of measles booster immunization. Conclusion: There is a relationship between the role of health workers, maternal interests, and the quality of health services on the provision of measles rubella booster immunization to toddlers aged 18–24 months in Pagar Gunung Health Center.